Enhanced modelling of heterogeneous gas–solid reactions in acid gas removal dry processes. (12th July 2016) - Antonioni, Giacomo; Dal Pozzo, Alessandro; Guglielmi, Daniele; Tugnoli, Alessandro; Cozzani, Valerio
Abstract: Acid gases as hydrogen halides and sulphur oxides are typical pollutants of combustion processes. Their removal from flue gas can be performed via the injection of dry powdered sorbents, as calcium hydroxide. However, the efficiency of dry treatment methods is hindered by the limited final conversion of the solid reactant, due to an abrupt decline of its reactivity during the reaction process. Fundamental gas–solid reaction models such as the shrinking core model and the grain model are able to reproduce this phenomenon only introducing an arbitrary value of the final conversion or an adjustable value of the solid-state diffusivity of the gaseous reactant. In the present study, the conventional grain model approach was integrated with a crystallisation and fracture (CF) submodel, which links the chemical potential of nucleation to the work needed to displace the layer of solid product formed on the reaction interface. The decline in reactivity of the sorbent was accounted by a twofold effect of the product layer growth: (i) the increase of the characteristic length for solid-state diffusion, accounted for in the grain model, and (ii) the increase of the mechanical work required for nucleation as a function of product layer thickness, accounted for in the CF submodel. This approach, validated against literature data on the Ca(OH)2 /HCl system, allowed reproducing the conversion of the solid reactant at different operating temperatures. Highlights: A low temperature-dependent final conversion of solid is reported in acid gas dry removal processes. An improved model was developed for acid gas reactions with dry powdered solid sorbents. A grain model approach was integrated with a crystallisation and fracture submodel. The model was validated against literature data on the Ca(OH)2 /HCl system. The model is able to account for the temperature-dependent final conversion of solid reactant.